Effect of Atherosclerosis on the Lateral Circumflex Femoral Artery and Its Descending Branch: Comparative Study to Nonatherosclerotic Risk. Issue 9 (September 2016) - Burusapat, Chairat; Nanasilp, Tirapat; Kunaphensaeng, Paiboon; Ruamthanthong, Anuchit
Abstract : Background: The anterolateral thigh (ALT) flap has been widely used for reconstructions. Nevertheless, the atherosclerotic risk factors that affect the lateral circumflex femoral artery (LCFA) are still inconclusive. The aim was to study the effect of atherosclerosis on the LCFA and descending branch (dLCFA) visualized by computer tomographic angiography (CTA) between nonatherosclerosis and atherosclerosis. Methods: Retrospective studies of CTA of lower extremity were reviewed. The patients were divided into 2 groups: nonatherosclerotic and atherosclerotic risk factors. The angiographic study of LCFA and dLCFA was analyzed, and atherosclerotic and nonatherosclerotic risk factors were compared. Results: Ninety-seven patients with 194 lower extremities were enrolled. Atherosclerotic risks comprised 76 patients. A total of 14, 16, and 46 patients had 1, 2, and 3 risk factors, respectively. Musculocutaneous perforator was 79.38%. The LCFA originated from deep femoral, common femoral, and superficial femoral artery was 97.42%, 2.06%, and 0.52%, respectively. The dLCFA was classified into 5 types depending on its origin. Diameters of LCFA in nonatherosclerotic and atherosclerotic patients were 4.03 ± 0.71 and 4.07 ± 0.97 mm, respectively. No statistical significance was found between both groups in diameters of LCFA. Diameters of dLCFA in nonatherosclerotic patients were 2.28 ± 0.28 mm and in atherosclerotic patients were 2.11 ± 0.28 mm. Statistical significance of diameters of dLCFA was found in patients having 3 risk factors and smoker groups ( p < 0.05). Conclusions: LCFA is not atherosclerosis resistant. Stenosis of the LCFA and dLCFA occurred in varying degrees in atherosclerosis-risk patients. Preoperative CTA should be considered to evaluate the patency in multiple risk factors patients.